Enhanced early hydration and mechanical properties of cement-based materials with recycled concrete powder modified by nano-silica. (1st June 2022) - Liu, Xiaoyan; Liu, Li; Lyu, Kai; Li, Tianyu; Zhao, Pingzhong; Liu, Ruidan; Zuo, Junqing; Fu, Feng; Shah, Surendra P.
Abstract: In recent years, an ever-increasing amount researchers dedicated themselves to exploring the possibility of introducing recycled concrete powder (RCP) into concrete as a substitute for cement. To optimize the effect of RCP on cement-based materials, this paper uses nano-silica (NS) to learn the hydration and mechanical properties of cement-based materials with RCP. The results indicated that after adding NS into RCP-cement pastes, the setting time of cement pastes was significantly reduced, while the samples' early hydration rate and hydration heat increased. Besides, the mechanical strength of the mortar decreased as RCP replaced part of the cement, while 2% NS can compensate for the mechanical strength loss of mortar caused by RCP as supplementary cementing materials. The X-ray computer tomography (X-ray CT) and mercury intrusion porosimetry (MIP) results showed that RCP increased mortar's pore volume fraction and porosity. In contrast, NS in RCP blended mortar significantly decreased the number of pores with a pore volume between 0.01 and 0.03 mm 3 and increased the proportion of harmless pores (From 28.6% to 31.4%). Hence, NS reduced the pore volume fraction and porosity of mortar. The results of X-ray CT and MIP showed that NS could refine the pore size in RCP blended mortar. X-ray diffraction (XRD) and scanning electron microscope (SEM) further revealed that the existence of NS can eliminate the adverse effects brought by RCP. Highlights: RCP was recycled as a substitute for cement. The effect of NS on the hydration of cement-based materials with RCP was investigated. 2% NS can compensate for the loss of mechanical strength of mortar blended with 30% RCP. The pore structure influenced by RCP and NS was studied by X-ray CT and MIP.